PENERAPAN MODEL PEMBELAJARAN INKUIRI TERSTRUKTUR BERBANTUAN VIRTUAL-LABORATORY PhET UNTUK MENINGKATKAN PEMAHAMAN KONSEP LISTRIK DINAMIS - Mamluatin Ni'mah; Wahono Widodo (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This study aimed to describe the implementation of learning, student responses, and the effect of learning with a structured inquiry learning model assisted by virtual-laboratory PhET to improve the mastery of the concept of dynamic electricity. This study was a pre-experimental design with one group pretest-posttest as a research design. Samples in this study were 26 students of IX grade in MTs Miksyaful Ulum. The data were collected using tests, questionnaire, and observation by applied in the form of written tests, student response questionnaires, and learning implementation observation sheets as the instruments. The findings revealed that: (1) the implementation of learning with a structured inquiry learning model assisted by virtual-laboratory PhET at the first and second meeting got a very good category, (2) the implementation of structured inquiry learning model assisted by virtual-laboratory PhET got positive responses from students with a very good category, (3) there were significant differences between understanding the concept before and after using a structured inquiry model assisted by virtual-laboratory PhET, and (4) the average value of N-gain of all subconcept got a high category. Therefore, learning with structured inquiry learning assisted by virtual-lab PhET can improve student conceptual understanding.